(untitled) (Cardiovascular Journal, 2023)
Background: Pediatric cardiac tumor is a very rare entity with an autopsy frequency 0.0017-0.28%. This study aims to analyze the characteristics and outcome of pediatric patients with myxoma. Methods: Nine Patients with myxoma treated between January 2008 & December 2019 were included into this retrospective study. The patients’ age ranged from 4 years to 11 years and weight from 10-20 kg. All patients were diagnosed by transthoracic echocardiography. Results: We did complete resection of tumor in all patients under cardiopulmonary bypass. Mean cardiopulmonary bypass time was 55 minutes & mean cross clamp time was 34 means. Mean ICU stay was 3 days. Six (66.33%) tumors found in left atrium, while 2 (22.11%) found in right atrium and 1(11.06%) in right ventricle. Histopathological report of all 9 tumors revealed myxoma. 1 patient developed left sided hemiparesis and another 1 patient developed wound infection. No mortality or recurrence in follow up period. Conclusion: Myxoma is the commonest primary cardiac tumor. Surgery of cardiac tumor can result in good early and long-term outcome. Cardiovasc j 2023; 15(2): 132-135